Embarazos y proyectos de vida de adolescentes atendidas en el subcentro Patria Nueva de la ciudad de Machala, año 2015 - Ojeda Aguilar, Ruth Berenice (2015)
Early pregnancies are risky, the body of the adolescents is still developing, they are not prepared physically even psychologically to play the role of mothers, to get a pregnancy at very early ages will clog up their life project and if the necessary medical cares are not taken properly it may cause the death of the newborn and his mother, a teenage girl in a period of gestation hinders her project life ,she couldn’t spend the enough time in her daily routines ,such as going out with friends ,sharing time in family and attending to an educational institution regularly.